Variants Of Resource Allocation Problem (International Journal of Engineering and Computer Science, 2017)
Consider the problem of allocating resources such as machines, memory or bandwidth to meet the demands of a given set of jobs. Resource allocation should be done in such a manner that the available resources are assigned to the given jobs in an economic way. The Resource allocation (RESALL) problem is motivated by its applications in many real-life scenarios such as interval scheduling, workforce management. This is an NP-hard problem. The input consists of a set of resources and a demand profile (corresponding to the set of jobs). Each resource has a capacity, a cost, a start time and a finish time. The cost of solution is the sum of the costs of the resources included in the solution. The goal is to find a minimum cost feasible solution such that multiple units of resources can be included in the solution and at any timeslot, the sum of capacities of these resources should be at least the demand requirement at that timeslot. This problem definition corresponds to the MULTIRESALL version of RESALL problem